2022
DOI: 10.1021/acs.langmuir.2c00037
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Solid Interfaces under Dynamic Shear Flow: Recent Insights into the Interfacial Slip

Abstract: The development of micro/nanofluidic techniques has recently revived interest in dynamic shear flow at liquid−solid interfaces. When the nature of the liquid−solid boundaries was revisited, the slip of the fluids relative to the solid wall was predicted theoretically and confirmed experimentally. This indicates that the molecular-level structures of the liquid−solid interfaces will be influenced by the liquid flow over certain temporal and spatial criteria. However, the fluid flow at the boundary layer still c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…SFG is a unique tool for studying the vibrational signatures of molecules at surfaces and interfaces, giving information on both surface and interfacial chemical species as well as molecular orientation. , SFG is a second-order nonlinear spectroscopy, which, according to the selection rules (under the electric dipole approximation), can generate a signal only from systems which lack inversion symmetry, including interfaces. , SFG can be performed on a number of interfaces, and a large body of work exists studying a variety of solid, liquid, gas, and buried interfaces. ,, Over the past decade, SFG has become a valuable tool for studying polymer surfaces and interfaces and has provided a great deal of information on adhesion chemistry. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…SFG is a unique tool for studying the vibrational signatures of molecules at surfaces and interfaces, giving information on both surface and interfacial chemical species as well as molecular orientation. , SFG is a second-order nonlinear spectroscopy, which, according to the selection rules (under the electric dipole approximation), can generate a signal only from systems which lack inversion symmetry, including interfaces. , SFG can be performed on a number of interfaces, and a large body of work exists studying a variety of solid, liquid, gas, and buried interfaces. ,, Over the past decade, SFG has become a valuable tool for studying polymer surfaces and interfaces and has provided a great deal of information on adhesion chemistry. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…As a binder, the PDA layer can effectively enhance the interfacial adhesion between the fabric and inorganic SiO 2 particles, , which plays an important role in the construction of the layered rough structure. In order to verify the adhesion of PDA layer, Figure a shows the morphology and structure of FAS-SiO 2 @fabric.…”
Section: Resultsmentioning
confidence: 99%
“…SFG is a second-order nonlinear optical spectroscopic technique, which provides vibrational spectra of surfaces and interfaces with a submonolayer sensitivity. Vibrational spectra are fingerprints of molecules; thus, SFG can be used to study the chemical composition and molecular structures at surfaces and buried interfaces. Selective information from surfaces/interfaces is obtained due to the selection rule of the SFG technique. Details of the theory of the method as well as experimental procedures and data analysis routines have been reported in a large number of previous studies and will not be described further here. I...…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we have examined the behavior of such an amphiphilic copolymer at the relevant solid/liquid interface using sum frequency generation (SFG) vibrational spectroscopy. SFG is a second-order nonlinear spectroscopic technique that can provide vibrational spectra of surfaces and interfaces with submonolayer specificity, which enables detailed characterization of the molecular structures of buried interfaces in situ and in real time. SFG experiments showed that poly­(MMA-co-MPEG350MA) adsorbs effectively on poly­(ethylene terephthalate) (PET) surfaces with deuterated aliphatic chains (d4-PET; see Figure S1 in the SI for the molecular structure of the substrate) from aqueous solutions at very low copolymer concentrations. PET was used as a model for synthetic cloth textiles, while deuteration was necessary to avoid spectral confusion in the SFG data.…”
Section: Introductionmentioning
confidence: 99%